The Effect of Bevacizumab and Curcumin towards the Process of Corneal Epithelization After Alkaline Trauma on Wistar Rat’s Cornea - Sri Inakawati (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: The purpose of this study is to know the difference between the effect of bevacizumaband curcumin as an antiangiogenesis towards the process of corneal epithelization on alkaline traumaon Wistar ratâ€™s cornea.Methods: Experimental research with post test only control design using 28 Wistar rats pure strain gotNaOH 1 M exposure with the diameter 1 mm in the central of cornea. Random sampling was dividedinto 4 groups which each group got bevacizumab 25 mg/ml, balanced salt solution (BSS), curcumin 80Î¼mol/l and dimethyl-sulfoxide (DMSO) 0.1% eye drops treatment for seven days, and the examinedthe process of epithelization of the cornea and the expression of vascular endothelial growth factor(VEGF) in the corneal epithelium.Results: We found very significant differences in corneal epithelization process after giving topicalbevacizumab 25 mg/ml and curcumin 80 Î¼mol/l on the alkaline trauma in the cornea of Wistar rats,where corneal epithelization on Curcumin is better than bevacizumab (p=0.027). An expression ofVEGF in corneal epithelium between the alkaline trauma on the pure strain of Wistar rat significantlyis different with p=0.00, which the expression on the provision of VEGF bevacizumab is lighter thanthe provision of curcumin.Conclusion: Giving curcumin on the alkaline trauma of Wistar rat resulted in better epithelization.The expression of VEGF in topical bevacizumab were lighter than the provision of curcumin.Â Keywords: bevacizumab, curcumin, BSS, DMSO, NaOH, corneal epithelization